The effect of the resources-based learning model in ecosystem learning to improve student learning outcomes - Teti Apriati; Syahruddin AR; Jamaluddin Jamaluddin; Baiq Sri Handayani (Jurnal Pijar Mipa, 2023)
This study aims to determine the effect of the Resource Based Learning (RBL) model in Ecosystem learning and its effect on biology learning outcomes at SMAN 3 Mataram. This type of research is research using a quantitative approach. The sample of this research was the students of class IX of SMAN 3 Mataram, which amounted to 32 students of X MIPA 1 for the control class and 32 students of X iMIPA i2 for the experimental class. The research data was obtained from a questionnaire on implementing the lesson plan and a learning outcome (post-test score) on ecosystem materials. The data analysis results show that the questionnaire score interval level for implementing the Resource Based Learning (RBL) model is 100% (very high). The conventional model shows the score interval that is implemented is 87.5%, and that is not implemented is 12.5%, and the level of validity of the questions in the cognitive domain, including the very valid criteria and the level of reliability of the questions in the cognitive domain, the criteria for reliable. The results of the data analysis of learning outcomes showed differences in the average post-test scores between the experimental class through the application of learning using the resource-based learning (RBL) learning model and the control class through the application of the conventional learning model. The post-test mean in the experimental class was 91.36, while the post-test mean in the control class was 71.69. The significance value of the count sample obtained is 0.532, the significance value obtained is greater than 0.05 Ho is rejected, and H1 is accepted, which means that the use of the Resource-based Learning (RBL) learning model is effective on student biology learning outcomes at SMAN 3 Mataram.